2010
DOI: 10.4248/ijos10008
|View full text |Cite
|
Sign up to set email alerts
|

Burning Mouth Syndrome

Abstract: Most clinicians dread seeing the patient presenting with a primary complaint of a burning pain on one or more oral mucosal surfaces. Unlike most other clinical conditions presenting in a dental office, burning mouth syndrome is poorly understood with few evidence based remedies. More recently, advances have been made towards clarifying the possible etiology of the disorder and testing the possible therapeutic modalities available. This article attempts to summarize the "state of the art" today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 19 publications
0
35
0
2
Order By: Relevance
“…Burning mouth syndrome is associated with nutritional deficiencies, including vitamin B 1 , B 2 , B 6 and B 12 deficiencies. However, recent studies have shown that zinc deficiency can also lead to BMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burning mouth syndrome is associated with nutritional deficiencies, including vitamin B 1 , B 2 , B 6 and B 12 deficiencies. However, recent studies have shown that zinc deficiency can also lead to BMS.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic endocrine and nutritional disorders might give rise to BMS. Some nutritional disorders include deficiencies in iron, zinc and vitamin B group, especially vitamin B 12 (6,7). pears in some patients with BMS with deficiencies mentioned previously, eliminations of systemic, local and psychological factors has results in alleviation of or decrease in BMS symptoms (8).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of pathogenic conditions therefore must be included such as local irritation; various mucocutaneous diseases; nutritional, metabolic, or endocrine disorders; xerostomia; and dysgeusia [3]. Kampo medicine, Japanese traditional herbal medicine, which originated in China, treats BMS based on Kampo-specific diagnostics, regardless of the pathogenesis determined on the basis of conventional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is most often bilateral, and does not conform to a single peripheral nerve distribution. 3 Burning mouth syndrome is associated in two thirds of cases with xerostomia and dysgeusia despite normal quantity of salivation, 5 and exhibits impaired olfactory perception.…”
mentioning
confidence: 99%
“…3 It affects more women, with a sex ratio of 7:1, 3,6 especially during perimenopause or postmenopause. 4 The age of onset is earlier in men than women (about 30 vs 50 years). 3 Burning mouth syndrome presents a difficult diagnosis for many clinicians for several reasons.…”
mentioning
confidence: 99%